Contributions of TGFJ31 and SMAD4 genes to the etiology of keloid scars in the Malay population - Khoo, Teng Lye
Background: Keloid scars are complex dermal condition with genetic and environmental contributing factors. TGF(3 and SMAD candidate genes, which are located in the same signaling pathway, are highly expressed in the keloid fibroblast cells. To date, only few documented reports showing relationship between TGF(31 and keloid in Caucasian population but none on SMAD4. Purpose: The contributions of TGF(31 and SMAD4 in the keloid formation of Malay population were studies. Subjects and Methodology: The DNAs were extracted from the blood samples of 1 00 Malay patients with keloids with another 100 healthy individuals without keloids as controls. The DNAs were analyzed via Polymerase Chain Reaction and single-nucleotide polymorphism genotyping. Results: TGF(31 halotypes showed a strong association with the risk of keloid formation. The CC halotypes of TGF(31, composed of both c.29C>T and -509T>C variants, showed higher frequency among keloid patients compared with the controls (11% versus 2.7%, corrected p=0.037), showing 4.5-fold increased risk for keloid formation. The c.5131A>G variant of SMAD4 revealed a statistically significant trend (p=0.0573). Taken together, either of these variants is the most probable causative factor at the expression level or is in linkage disequilibrium with other causative variants in a complex pattern with the environmental factors, contributing to keloid formation. Conclusion: This is the first study documenting strong positive association between TGF(31 and SMAD4 variants and keloid formation in the Malay population.